KEANEKARAGAMAN BAKTERI PENGHASIL SELULOSA PADA HABITAT ALAMI BERBAGAI JENIS BUAH DAN INOKULUM NATA - , SRI HUSNIATIL HULUWI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The study of diversity of cellulose-producing bacteria was conducted by isolating the bacteria from their natural habitats such as fruit and inoculums of nata fermentation. Bacteria were selectively isolated using media HS (Hestrin and Schraam) and screened then ability to produce cellulose using the medium of coconut water containing 5% glucose and 0.5% ammonium sulfate at pH 5. Furthermore, the isolates of cellulose-producing bacterial were characterized and identified using phenotypic and molecular characters. The result showed that 29 isolates of celluloseproducing bacteria were successfully obtained from their natural habitats, , that is fruit (grape, oranges, barked, mango) and inoculums of nata fermentation. The entire group of isolates were rod-shaped gram-negative bacteria and able to oxidize ethanol to acetic acid, thus identified as members of family Acetobacteraceae. The results of matching profile characterization and identification are showed that the overall isolates grouped in three different genera, namely Acetobacter, Gluconacetobacter, and Gluconobacter. There were 12 isolates which could be grouped in to the genus Acetobacter, which were identified as strain members of five different species, namely A. pasteurianus (MGA2), A. orleansis (MGA1), A. lovoniensis (SLK1, JRK3, MGA6), A. indonesiensis (AGR7, AGR8, AGR9, AGR10, AGR 17) and A. tropicalis (JRK1, MGA5). While 10 and 7 isolates were identified to be number of the genus Gluconacetobacter, and Gluconobacter, subsequently. 10 isolates which were grouped in the genus Gluconacetobacter were, then identified as strain members of five different species, namely Ga. hansenii (GDN25, AGR18, AGR19), Ga.oboediens (GDN31), Ga. xylinus (JRK2), Ga. swingsii (NDCI11, NDCI122), and Ga. rhaeticus (GDN23, NDCI13). Furthermore, the 7 isolates which were grouped in the genus Gluconobacter were, then identified as strain members of three different species, namely G. oxydans (TNI26, GDN32), G. cerinus (GDN32, MGA4, AGR3, AGR4), and G. thailandicus (MGA3). Phylogenetic analysis based on 16S rRNA gene sequences are shown that the isolates MGA6 and MGA3 both identified as strain member of the species A. lovoniensis.